2011
DOI: 10.1002/btpr.711
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the enzymatic digestibility of sugarcane bagasse through the application of an ionic liquid in combination with an acid catalyst

Abstract: Various ionic liquids have been identified as effective pretreatment solvents that can enhance the cellulose digestibility of lignocellulose by removing lignin, one of the main factors contributing to the recalcitrant nature of lignocellulose. 1-Butyl-3-methylimidazolium methylsulfate ([BMiM]MeSO(4)) is a potential delignification reagent, hence its application as a pretreatment solvent for sugarcane bagasse (SB) was investigated. The study also evaluated the benefit of an acid catalyst (i.e., H(2) SO(4)) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…However, in pretreatment of sugarcane bagasse catalyzed by acid, using HCl- [Bmim] [Cl] [132] [133], cellulose crystallinity remained unaltered even though a significant increase of cellulose digestibility was achieved. The authors suggested that digestibility increase was due to the highly effective and simultaneous removal of xylan and lignin that facilitated cellulose enzymatic saccharification efficiency.…”
Section: Ionic Liquid Pretreatmentmentioning
confidence: 99%
“…However, in pretreatment of sugarcane bagasse catalyzed by acid, using HCl- [Bmim] [Cl] [132] [133], cellulose crystallinity remained unaltered even though a significant increase of cellulose digestibility was achieved. The authors suggested that digestibility increase was due to the highly effective and simultaneous removal of xylan and lignin that facilitated cellulose enzymatic saccharification efficiency.…”
Section: Ionic Liquid Pretreatmentmentioning
confidence: 99%
“…This result indicated that acid pretreatment in IL was superior to conventional acid pretreatment in water. According to previous study [21], below the glass transition temperature of lignin (<160°C), a digestible biomass was slightly produced in the absence of IL. Therefore, we believe the absence of an IL caused the low production of glucose.…”
Section: Resultsmentioning
confidence: 70%
“…Aqueous ionic liquid pretreatment solvent with two catalysts Acid-catalyzed pretreatment in IL has usually been combined with at least one kind of acid for improvement [19][20][21]. On the other hand, in the case of diluted acid pretreatment for the biomass in a water system, several studies have shown that inorganic salts also indicate the possibility of improvement for the hydrolysis rate of the hemicellulose and cellulose in biomass [22,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment of different agricultural residues, with the aid of a 15-L reactor steam gun, has been evaluated with South African sponsored research funding in anticipation of an emerging cellulosic ethanol industry. [115][116][117][118] Researchers have also developed the capacity to generate pyrolysis and gasification products from different cellulosic feedstocks to substitute fossil fuels such as coal, coking coal and reductants. 119,120 These studies also support developments toward the realisation of a bio-economy.…”
Section: Volume 111 | Number 5/6mentioning
confidence: 99%